Genome-Wide Association Study Reveals Candidate Genes Involved in Fruit Trait Variation in Persian Walnut (Juglans regia L.) - Bernard, Anthony; Crabier, Julie; Donkpegan, Armel S. L.; Marrano, Annarita; Lheureux, Fabrice; Dirlewanger, Elisabeth (Frontiers in Plant Science, 2021)
Elucidating the genetic determinants of fruit quality traits in walnut is essential to breed new cultivars meeting the producers and consumers’ needs. We conducted a genome-wide association study (GWAS) using multi-locus models in a panel of 170 accessions of Juglans regia from the INRAE walnut germplasm collection, previously genotyped using the AxiomTMJ. regia 700K SNP array. We phenotyped the panel for 25 fruit traits related to morphometrics, shape, volume, weight, ease of cracking, and nutritional composition. We found more than 60 marker-trait associations (MTAs), including a highly significant SNP associated with nut face diameter, nut volume and kernel volume on chromosome 14, and 5 additional associations were detected for walnut weight. We proposed several candidate genes involved in nut characteristics, such as a gene coding for a beta-galactosidase linked to several size-related traits and known to be involved in fruit development in other species. We also confirmed associations on chromosomes 5 and 11 with nut suture strength, recently reported by the University of California, Davis. Our results enhance knowledge of the genetic control of important agronomic traits related to fruit quality in walnut, and pave the way for the development of molecular markers for future assisted selection.